Hearing loss and risk factors among community dwelling older adults in Selangor - Siti Zamratol-Mai Sarah Mukari,; Nashrah Maamor,; Wan Syafira Ishak,; Wan Fazlina Wan Hashim, (Penerbit Universiti Kebangsaan Malaysia, 2016)
There is a lack of population-based data on prevalence of hearing loss in Malaysia. The purpose of this population-based study was to determine the prevalence of hearing loss and its risk factors among 382 older adults aged 60 years and above, recruited through multistage random sampling in Selangor. Hearing level was measured using pure tone audiometry. Hearing loss was classified into at least mild hearing loss and significant hearing loss based on the pure tone average (PTA) of 0.5, 1, 2 and 4 kHz. The examination also included face-to-face interview on hearing related medical history, noise exposure and hearing aid use. Overall, the prevalence of at least mild hearing loss and significant hearing loss were 73.6% (95% CI: 69.4 - 77.4) and 24.6% (95% CI: 20.8 - 28.7), respectively. The odds for at least ‘mild hearing loss’ were male gender, Chinese ethnicity, residing in urban areas, had no formal education or primary school education and history of hypertension. The risk for ‘significant hearing loss’ was significantly higher in males, those who lived in urban areas and elderly with cognitive impairment. Chinese and Indian ethnicities had significantly lower risks than Malay ethnic to have significant hearing loss. Despite the high prevalence of hearing loss, only 4.4% who might benefit from hearing aids wore them. In conclusion, findings from this study show high prevalence of hearing loss among the elderly population. Given the significant association between hearing loss and cognitive impairment, future studies should explore the role of hearing amplification in alleviating or slowing the progress of cognitive decline.